ANALISA PERBANDINGAN QUERY PENCARIAN MENGGUNAKAN FUNGSI MATCH-AGAINST PADA MYSQL DENGAN TABEL KAMUS - Zudha Pratama; Yans Safarid Hudha; M Lukman Prayoghi (CCIT Journal, 2018)
Virtually all database-related systems provide search features. Starting from a complex search engine like google to a relatively simple example of search features on a digital library page. A good search engine is capable of delivering fast, accurate, and fault-tolerant results. Speed ​​may be affected by server device capabilities and complex algorithm combinations.The form of the condition condition used in the search query generally uses LIKE for partial search, REGEXP for multi key search, and MATCH-AGAINST for multi key search with fulltext index. However, these functions are not sufficient to perform a search selection on a slightly wrong key or rather fault tolerance that is still not good. So researchers do an analysis if one of the search function is combined with a dictionary table.Table dictionary as a comparator key to find a more appropriate key if key wrong key. But on the other hand the addition of the comparison process is estimated to have a weakness to the processing time. Researchers assume if the weakness can be overcome if the ability of the server is improved.